EEG before and after total corpus callosotomy for pharmacoresistant infantile spasms: Fast oscillations and slow‐wave connectivity in hypsarrhythmia. (13th August 2019) - Baba, Shiro; Vakorin, Vasily A.; Doesburg, Sam M.; Nagamori, Chizuko; Cortez, Miguel A.; Honda, Ryoko; Ono, Tomonori; Toda, Keisuke; Nishimoto, Hanako; Ebihara, Toshihiro; Sakai, Kana; Ochi, Ayako; et al.
Abstract: Objective: We analyzed the features of fast oscillations (FOs) and connectivity in hypsarrhythmia to identify biomarkers for predicting seizure outcomes after total corpus callosotomy (TCC) in children with pharmacoresistant infantile spasms (IS). We hypothesize that the power of FOs and connectivity of slow waves in hypsarrhythmia would indicate the prognosis of IS. Method: We retrospectively identified 42 children with pharmacoresistant IS who underwent TCC from 2009 to 2014 at Nagasaki Medical Center. We collected preoperative hypsarrhythmia for 200 seconds from each child. Children were categorized into three groups with interictal epileptic discharges on EEG at 6 months after TCC: group A, no epileptic discharge; group B, lateralized epileptic discharges; and group C; bilateral epileptic discharges. We analyzed spectral power and phase synchronization in preoperative hypsarrhythmia among the three groups. Results: We found 10 children in group A, 10 children in group B, and 22 children in group C. All group A and 1 in group B achieved seizure freedom after TCC. Six (67%) of 9 group B children who underwent further surgeries achieved seizure freedom. Ten (45%) of group C children had seizure reduction >50% after TCC, and 13 (87%) of 15 children who underwent further surgeries had residual seizures. The clinical profiles of the three groups did not differ significantly. The power of FOs (≥45 Hz) in hypsarrhythmia was significantly stronger in group C at the midline and temporal regions than in groups B and A ( P  =   .014). The connectivity of theta (4‐9 Hz) and FOs (29‐70 Hz) tended to increase in group C, compared with the increased connectivity of 1‐2 Hz in group A ( P  =   .08). Significance: The increased power and connectivity of FOs in hypsarrhythmia may correlate with pharmacoresistant and surgically resistant seizures in IS. The existence and connectivity of FOs are associated with unilateral/bilateral cortical epileptogenicity in hypsarrhythmia. Prominent slow waves and connectivity without FOs might correlate with seizure freedom after TCC. Modulation of the callosal system with subcortical/cortical epileptic discharges might play a role in generating hypsarrhythmia and IS.